PENGEMBANGAN SISTEM PENGOLAHAN LIMBAH PABRIK BATUBARA CAIR - Fatimah, Nevi; Soleh, Soleh (Badan Pengkajian dan Penerapan Teknologi, 2006)
Coal liquefaction process ( BCL Process) becide produce liquid fuel also liquidwaste that contains amonia, phenols and other organic matter in highconcentration. This waste must be proceess before releasing to the environmen.Tthe processing system to treat the waste must efficient and competent toovercome some problems may occur during processing. In this paper will discussthe investigation and experiment for liquid waste treatment designed for coalliquefaction plant.This plant will produce amonia by stripping, phenol by solventextraction that will be reduction by fluidization media system. This system wasapplied for Brown Coal Liquefaction (Victoria) Pty. Ltd and showed very effectiveto cacth phenols and others organic matter.Kata kunci: waste treatment, coal liquefaction plant, coal liquefied oil